The Criminal Law and the Private Security - Deanoska Trendafilova, Aleksandra (Филозофски факултет – Скопје/Faculty of Philosophy – Skopje, Институт за безбедност, одбрана и мир/Institute of security, defence and peace, 2016)
The criminal law and the private security are undoubtedly connected. Namely, the criminal law as a part of the legal science that has accessory dimension protects different individual and collective rights and liberties and other goods and values. The legally set objective of the private security is "prevention and detection of harmful activities and illegal actions that threaten the physical integrity and dignity of the person and property". This unquestionably implies a connection with some fundamental institutions of the criminal law. In respect with the criminal substantive law, private security workers need to act within the limits of the provisions of the Criminal Code for the illegality as an element of the offense, the provisions on self-defense and extreme necessity, the foundations and boundaries of the exclusion of illegality, unlawful arrest, the incriminations against violations of life and body, crimes against property, privacy etc. Some criminal procedural aspects are also relevant to private security primarily the detention within the boundaries set for perpetrators in flagranti. Another important, yet divergently set segment of this relationship is the possibility of private security workers also to appear in the role of perpetrators of criminal offenses and misdemeanors by exceeding and abusing their powers. The paper also sets out the main areas of the criminal legislation significant for the private security workers.
Keywords: criminal law, private security, criminal offence, illegality